Rememorando - Ureña, Jurgen, 1973-; Jiménez, Hernán; Fallas, Katzuomi (Producciones La Ventana, 2007)
Rememorando makes a parable about the Central American struggle against the so-called "filibusters" of William Walker, slavers of the southern United States that in the mid-nineteenth century intended to annex at least part of the Central American isthmus, in that turbulent era of identity and national tensions. --